Patient satisfaction after cataract surgery using visual functioning questionnaire - Shakeel, Sidra; Kazi, Umer; Qazi, Asif Mashood; Memon, Muhammad Saleh; Memon, Fateh; Khan, Hina; Tariq, Anas (International Journal of Research in Medical Sciences, 2019)
Background: NEI VFQ-25 questionnaire is widely used to determine different health benefits to patient’s daily activities, social and mental health. The objective of this study was to determine satisfaction of patients undergoing cataract surgery. Methods: After ethical approval, a cross-sectional study using non-probability convenient sampling technique was done. Post-operative cataract patients between 18-75 years of both gender were included and patients reluctant to participate, <18 years of age or above 75 were excluded. SPSS version 20 was used for data analysis. Scoring of NEI VFQ-25 questionnaire was done. Chi-square test was applied between groups of patients with or without glasses using distant and near visual acuities keeping p-value of ≤0.05 as significant. Results: Mean age of 100 patients was 58.56±9.63 years, 78 patients were female housewives. Significant improvements in visual acuities was reported with distant or near vision with or without glasses after cataract surgery (p-value <0.01). Patient’s difficulties in worrying with eye sight, reading newspapers, reading stuff well up close, reading street signs, having issue in visiting others, going out to movies/plays, feeling of accomplishing less, having limited endurance and need for help from others in order to perform visual tasks were associated independently with reduced visual acuity and visual impairment. Conclusions: Cataract surgery significantly improved patients’ visual acuities, daily activities, mental and social health issues. Most patients were satisfied with cataract surgery and had fulfilling improvements to post-operative quality of life.